Problems in supplying modern internal combustion engine with biofuels - Biernat, Krzysztof; Jeziorkowski, Adrian (Studia Ecologiae et Bioethicae, 2008)
The paper presents most popular biofuels with their basic physicochemical properties in comparison with conventional fuels, the article also contains present normalizations of selected alternative fuels, the possibilities of supplying modern internal combustion engine with biofuels with requiring changes in their constructions were estimated on the basis of collected documentation.